2014
DOI: 10.4103/0301-4738.116464
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative visual loss with non-ocular surgery: Case report and review of literature

Abstract: Perioperative visual loss (POVL), a rare but devastating complication, has been reported after spine, cardiac, and head-neck surgeries. The various causes include ischemic optic neuropathy, central or branch retinal artery occlusion, and cortical blindness. The contributory factors described are microvascular diseases and intraoperative hemodynamic compromise. However, the exact association of these factors with post-operative blindness has not yet been confirmed. A case of POVL with caesarian section surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Arterial occlusions have been reported after nonophthalmic invasive procedures such as spine, cardiac, and head-neck surgeries; hip/femur fracture repair; knee replacement; appendectomy; colorectal resection; and cholecystectomy. 8 In our 4 cases, RAOs were noted after cardiac surgery and neurosurgeries. Warner et al found hypercoagulability, perioperative hypotension, sickle cell disease, diabetes mellitus, embolic sources, prone positioning, ocular compression, increased intraocular pressure, and anemia to be risk factors for perioperative visual loss, but we did not identify these factors in any of our patients.…”
Section: Discussionmentioning
confidence: 61%
“…Arterial occlusions have been reported after nonophthalmic invasive procedures such as spine, cardiac, and head-neck surgeries; hip/femur fracture repair; knee replacement; appendectomy; colorectal resection; and cholecystectomy. 8 In our 4 cases, RAOs were noted after cardiac surgery and neurosurgeries. Warner et al found hypercoagulability, perioperative hypotension, sickle cell disease, diabetes mellitus, embolic sources, prone positioning, ocular compression, increased intraocular pressure, and anemia to be risk factors for perioperative visual loss, but we did not identify these factors in any of our patients.…”
Section: Discussionmentioning
confidence: 61%
“…PION diagnosis requires imaging, because there are no visible structures to be evaluated with clinical examination. [14][15][16][17] Generally, CRAO is caused by direct pressure over the eye, augmenting intraocular pressure and compromising perfusion. In prone position, which is the most common position for the patients in spine surgery, the head should be at the same level as the heart.…”
Section: Discussionmentioning
confidence: 99%
“…discussed in 2014 various etiologies of POVL following prone spine surgery; this included ION, CRAO or branch retinal artery occlusion, and CB largely due to microvascular pathology and/or intraoperative hypotension [Tables 3 and 4 ]. [ 28 ] This study uniquely presented POVL following a cesarean section.…”
Section: Review Articles On Postoperative Visual Loss With Prone Spinmentioning
confidence: 99%